Serum Ferritin Level as a Predictor for Intra Uterine Growth Restriction - Faisal Mohammed, Inaam; Hassan Abass, Rukaia; Ahmed Ali, Taha; Khalaf Abbas, Maysaloon (Diyala Journal of Medicine, 2024)
Background: Maternal serum ferritin is being explored as a potential predictor for Intrauterine Growth Restriction (IUGR). Early detection of IUGR is crucial for improving perinatal outcomes and reducing associated mortality and morbidity. Objective: To evaluate the role of elevated maternal serum ferritin in predicting the risk of developing IUGR. Patients and Methods: A prospective case-control study was conducted at Al-Batool Teaching Hospital, Diyala, involving 51 pregnant women divided into two groups based on pregnancy status. Demographic data, obstetric history, and risk factors for IUGR were collected through a questionnaire, and blood samples were taken to measure hemoglobin and serum ferritin levels. Results: The study found that the mean serum ferritin level was significantly higher in the patient group (209.89±50.95 ng/ml) compared to the control group (66.91±37.49 ng/ml), with a p-value of <0.001. The mean birth weight was significantly lower in the patient group (1873.81±425.62 g) compared to the control group (3078.67±415.56 g), also with a p-value of <0.001. There were no significant differences in age and hemoglobin levels between the two groups. Conclusion: Elevated maternal serum ferritin levels may suggest an increased risk of IUGR, emphasizing the need for further research to validate its role as a predictive marker.